Character Education as Mental Development for Students of MTs Irsyadussalam Cakkeware, Bone Regency - Darnanengsih; Rusyaid (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2023)
This study found that character education at MTs. Irsyadussalam Cakkeware Bone Regency has been implemented. This can be seen from the mental picture of students at MTs. Irsyadussalam Cakkeware is good, but still needs development. The process of character education as a mental development of students has been carried out in several stages starting from integrating character values into learning activities, understanding and appreciation of character values, and the involvement of all school communities in the mental development of students. In addition, the results of the implementation of character education as the mental development of students are carried out in several ways, namely by way of exemplary and habituation of doing good, habituation to praying duhur in congregation at school, and holding the Qur'an tadarus which becomes a routine every night at the Irsyadussalam mosque, as well as reading barzanji every Friday at school. However, it cannot be said to be running optimally, because there are still some students who show behavior that does not reflect as students, lack of self-awareness, lack of concern for the environment, less polite to teachers and friends, still like to hang around during class hours, less attention to neatness, and some are even found smoking secretly. This is where the importance of character education as a mental development of students. As an implication, MTs. Irsyadussalam Cakkeware Bone Regency is expected to further improve the implementation of character education as a mental development of students. The process and forms of implementation results are further improved to create a generation with character, a generation that has a good mentality to avoid immoral behavior.